PERCEIVED EFFECTS OF JOB STRESS ON THE WORK BEHAVIOUR AND ATTITUDE OF NURSES TOWARDS PATIENTS IN THE UNIVERSITY OF ILORIN TEACHING HOSPITAL (UITH), NIGERIA - Abdulhameed, Abdussalam; Damilare Emmanuel, Wemimo; Kayode Ibrahim, Abdullahi (African Journal of Social and Behavioural Sciences, 2024)
The study examined the perceived effect of job stress on nurses’ work behaviour and attitude toward patients in the University of Ilorin Teaching Hospital. It aimed at tackling how job stress can be adequately and effectively managed by the nurses, hospital management, and government to avoid unnecessary negative attitudes of nurses towards patients that may adversely affect the quality of services provided. The study adopted a Correlational research survey. A convenient sampling technique was adopted, and the sample size was 150. However, 145 questionnaires were recovered from the participants, and eight in-depth interviews (IDI) were conducted to support the stance of the quantitative data. Three hypotheses were formulated and tested at a 0.05 level of significance. The first hypothesis was rejected because there is a significant effect of job stress on the attitude and work behaviour of nurses toward patients; the second was accepted because there was no significant effect of job stress on the relationship among nurses; the third hypothesis was rejected because there is a significant effect of job stress on the quality of care given to patients by nurses. The study concludes that job stress significantly affects nurses’ work behaviour and attitude towards patients. Therefore, the study recommends that the government and other stakeholders give the welfare of the nurses’ utmost priority in the hospital setting, which will boost the morale of nurses to cope with the working conditions they find themselves in. The government and hospital management should implement policies allowing work flexibility amongst nurses, preventing them from experiencing frequent stress.